FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PAMBOANG - Irmayanti AR (Jurnal Kesehatan Marendeng, 2023)
Abstract. This study aims to determine the risk factors for anemia in pregnant women at the Pamboang Community Health Center, Majene Regency in 2022. The method used is observational with a cross-sectional approach. The results of this study to find out what factors influence the incidence of anemia in pregnant women at the Pamboang Community Health Center. This research was conducted with 110 pregnant women who met the inclusion criteria using the total sampling method and using a checklist measuring instrument. Data analysis technique using the SPSS program chisquare. From the results of the chisquare test, there is no significant relationship between the incidence of anemia in pregnant women and KEK with a value of p=0.825 and there is no significant relationship between the incidence of anemia in pregnant women and parity with a value of p=0.158 and there is no significant relationship with the incidence anemia in pregnant women with age with a value p=0.575. The conclusion of this study is that there is no significant relationship between KEK, parity and age and the incidence of anemia in pregnant women at the Pamboang Public Health Center, Majene Regency in 2022.